Earthquake Damage Intensity Relationship for Residential Houses in West Sumatra - Ismail, Febrin Anas; Hakam, Abdul; Fauzan, Fauzan (UI Scholars Hub, 2012)
The Sumatra 30 September 2009 earthquake has damaged hundred thousand buildings in West Sumatra Province. The earthquake is located in 100 km offshore of Padang City, the Capital City of the province. Survey has been conducted to assess the damage of the building in few days after the earthquake. In this survey, the damage of buildings are categorised into 3 level that are heavily, moderate and slightly damages. This paper explores the level damage of building and then the intensity of the shaking in the affected area. Then based on the coordinate of every building location, the buildings are scattered in a map together with the intensity level. The relationship between the damage level and intensity for West Sumatra then is developed. This special damage-intensity relation is very important to be used for predicting the damage level due to a specified earthquake. The damage level is needed by The Government to develop an emergency and reconstruction budget plan for earthquake disaster in future.